2017
DOI: 10.1590/s0102-865020170050000004
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the ERK1/2 and PI3K/PKB signaling pathways in regulating the expression of extracellular matrix genes in rat pulmonary artery smooth muscle cells

Abstract: Roles of the ERK1/2 and PI3K/PKB signaling pathways in regulating the expression of extracellular matrix genes in rat pulmonary artery smooth muscle cells The pulmonary artery was then extracted, the fibrous tunica externa dissected and the runica intima stripped. The myogenous tissues of the vascular middle layer of the artery were then cut into 1 mm³ tissue blocks, and seeded into the culture flasks with the density as 1cm -2 . After 2 h wall-adherent cultivation at 37°C and 5% CO 2 , M199 medium containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“… 25 Also, inhibitors such as ERK1/2 can promote apoptosis, reduce their biological activates, and inhibit the conversion of cellular phenotype by inhibiting the deposition of extracellular matrix in malignant mesothelioma cells. 26 A previous study demonstrated that higher concentrations of HCF could lead to higher mRNA levels of ERK1/2, 27 which is in consensus with our study. Also, PCNA, a key coordinator of DNA replication, is involved in DNA processes such as DNA repair and chromatin/epigenetic maintenance.…”
Section: Discussionsupporting
confidence: 93%
“… 25 Also, inhibitors such as ERK1/2 can promote apoptosis, reduce their biological activates, and inhibit the conversion of cellular phenotype by inhibiting the deposition of extracellular matrix in malignant mesothelioma cells. 26 A previous study demonstrated that higher concentrations of HCF could lead to higher mRNA levels of ERK1/2, 27 which is in consensus with our study. Also, PCNA, a key coordinator of DNA replication, is involved in DNA processes such as DNA repair and chromatin/epigenetic maintenance.…”
Section: Discussionsupporting
confidence: 93%
“…CTGF also promoted collagen synthesis [ 47 49 ], which may explain the increased deposition of type I and type III collagen in the prevascularized scaffolds at 4 weeks post operation (Fig. 4B ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have focused on the possible signaling pathways of EMT (2,38,47). The precise regulatory mechanism of the EMT process involves extracellular signal transduction to the cell via specific binding to a receptor on the membrane, leading to the initiation of a variety of signaling pathways to activate transcription factors in the nucleus and finally regulate the expression of EMT-related genes (36,37).…”
Section: Discussionmentioning
confidence: 99%